Profil Laboratorium Dan Pelaksanaan Praktikum Biologi Di SMA Negeri 1 Kartasura Tahun Ajaran 2015/2016 - PARAMITA, Adhe; , Dra. Hariyatmi, M.Si (2016)
The hallmark of learning biology is their lab activities both in the laboratory and in nature. Practical implementation should be supported by biology laboratory facilities and infrastructure that must be in accordance with the strictest standards in the laboratory Permendiknas No.24 of 2007. This study aims to determine the suitability of biology laboratory facilities and infrastructure in SMA Negeri 1 Kartasura with the standard provisions biology laboratory by Permendiknas 24 of 2007 and analyze the implementation of practical biology lesson in SMA Negeri 1 Kartasura. Data collection techniques in research techniques used are observation, interviews, and questionnaires. This type of research is qualitative descriptive. The study was conducted in November 2015 until June 2016 in SMA Negeri 1 Kartasura. Results show that: 1) the suitability of biological laboratory facilities and infrastructure based Permendiknas 24 of 2007 seen from seven indicators earn a percentage of each: a) infrastructure 100% (is appropriate), b) 96.4% furniture (not appropriate ), c) props 60% (not appropriate), d) the tools and experimental materials 65.2% (not appropriate), e) media education 100% (is appropriate), f) consumables 100% (was appropriate) , g) other equipment 60% (not appropriate). 2) the implementation of laboratory work in biology learning in SMA Negeri 1 Academic Year 2015/2016 Kartasura views of five indicators earn a percentage of each: a) the suitability of the material practicum 100% (excellent), b) the amount of practical implementation 40% (less) c) the interest of students to the lab 81% (excellent), d) the preparation and practical implementation 76% (good), e) constraints practical implementation 37% (less). The conclusions of this study were 1) infrastructure biology laboratory at SMA Negeri 1 Kartasura based Permendiknas 24 of 2007 with an average percentage of 83.1% (not appropriate) pertained not meet the minimum standard of 100% listed in Permendiknas 24 in 2007, 2) the implementation of laboratory experiments biology SMA Negeri 1 Kartasura relatively good with an average percentage of 66,8%.